IL-10 derived from Hepatocarcinoma cells improves human induced regulatory T cells function via JAK1/STAT5 pathway in tumor microenvironment. (May 2021) - Zhang, Shaopeng; Gan, Xiaojie; Qiu, Jiannan; Ju, Zheng; Gao, Ji; Zhou, Jinren; Shi, Chengyu; Zhu, Yaqing; Li, Zhang
Highlights: Hepatocarcinoma cells (HCC) derived supernatants inducing decreased apoptosis and greater stability of Foxp3 in human iTreg cells. Pro-inflammatory cytokines in iTregs are inhibited by HepG2 Supernatants. Supernatants derived from HCC also reverse IL-1β/6 triggered decline on Foxp3 in iTregs. Improved stability and function of HepG2 supernatants treated iTregs is IL-10—JAK1—STAT5 signal pathway-dependent. Abstract: Forkhead box P3 (Foxp3) expressing CD4 + CD25 + regulatory T cells (Tregs), an essential subset of immune T cells for maintaining immune homeostasis is implicated as a negative regulator in an anti-tumor immune response. Current researches suggest that reducing tumor-infiltrating Tregs contribute to enhanced anti-cancer effect. However, the mechanism of infiltration of a large number of Tregs into tumor tissues is still unclear. In this study, human induced Tregs (iTregs) were co-cultured with human hepatocytes and various types of cancer cells (HepG2, NSCLC, and AsPC-1) supernatants. Foxp3, multiple cytokines, levels of apoptosis and suppressive ability of iTregs were detected by FACS. Western blot was employed to test of proteins. Impact of HepG2 supernatants on T cell subpopulations differentiation, cytokines in supernatants were examed by FACS and ELISA respectively. Anti-IL-10R antibody and JAK1 inhibitor were used to reconfirm the role of tumor-derived IL-10 play in the regulation on iTregs. Hepatocarcinoma cells (HCC) supernatants treatment increases Foxp3 stability and reduces apoptosis level in human iTregs without influencing its differentiation trend. Furthermore, IL-10 was found to be extremely higher in HCC supernatants than other groups, IL-10R blockade neutralize the effect of HCC supernatants on iTregs in vitro obviously. HCC supernatants also reversed IL-1β/6 triggered decline on Foxp3 which may be related to higher expression of JAK1 and elevated phosphorylation level of STAT5 induced by IL-10. Our results suggest that improved stability and abnormal accumulation of Tregs in tumor microenvironment is IL-10/JAK1/STAT5 signal pathway-dependent and provide a novel approach for improving the efficiency of anti-tumor immunotherapy.